Changes in cortisol concentrations during early development and larval metamorphosis in the Feshwater catfish, Heteropneustes fossilis (Bloch) - NAYAK, P K; MISHRA, J; MISHRA, T K; AYYAPPAN, S (The Indian Journal of Animal Sciences, 2014)
The cortisol content of whole- animal was measured in embryo and larvae of freshwater catfish (Heteropneustes fossilis) by radioimmunoassy. The total cortisol content of fertilized eggs was 3.8+-0.4 ng/g wet wt., which decreased gradually during embryonic development and attained minimum levels during the completion of yolk sae aborption. In the larvae the levels significantly increased on seventh day onwards and peak levels attained on 15th-day-old larvae (8.8=-0.9 ng/g wet wt). The presence and clearance of cortisol during early development of fertilized eggs and embryonic develpment indicated its utilization. However, enhanced cortisol concentration in the post larvae emphasized cortisol secretion by larval interrenal gland, where peak levels of cortisol prior to the metamorphic transformation of larvae to juvenile in this species suggests functional significance during metamorphic events in H. fossilis.